Regulation of network sectors in the EU: A federalist perspective - Wolfgang Kerber; Julia Wendel (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
The vertical allocation of regulatory powers within the European two-level system of network sector regulation is analysed from the perspective of the economic theory of legal federalism. The analysis shows that sophisticated combinations of harmonised European rules along with sufficient scope for decentralised decisions of national regulators seem to be optimal. Especially interesting is that networks of regulatory authorities (as BEREC in telecommunications) can play an important role in regard to balancing the advantages and disadvantages of (de)centralisation. Whereas in regard to telecommunication a further shifting of regulatory powers to the EU level cannot be recommended, both in energy and railway markets it might still be necessary to strengthen the regulatory power of the EU.
Keywords: K23; H77; F15; 330; EU sector regulation; legal federalism; regulatory networks; telecommunication